Calidad de vida relacionada con la salud en pacientes con artritis reumatoide tratados en una IPS especializada, Medellín 2012 (2013)
ABSTRACT: To determine the health-related quality of life as well as some of its associated factors among patients with rheumatoid arthritis attending the healthcare-providing institution selected for this study, which was located in the city of Medellín. Methodology: a cross-sectional study was conducted on a representative sample of 366 patients, and the data was obtained using the sf-36, a generic instrument for measuring health-related quality of life. Results: the average age of patients was 56 (sd = 12.9), and individuals were predominantly female (91%). Retired patients as well as patients suffering from depression or cardiovascular diseases reported that their health status was worse than or equal to that of the previous year. The median scores for the emotional role, social function, and mental health domains ranged from 68 to 100 points out of a total score of 100. As for physical role, body pain, and physical function, their values varied from 41 to 55 points. Men obtained lower scores for general health than women. Likewise, patients who were retired, depressed, or from the low or medium socioeconomic levels obtained low general health scores in most domains of the SF- 36. Recommendation: the authors propose a psychosocial intervention aimed at improving the quality of life of the patients, particularly that of the individuals who are depressed, retired, or from the low or medium socioeconomic levels.